2011
DOI: 10.3892/ijo.2011.1298
|View full text |Cite
|
Sign up to set email alerts
|

The curcumin analogue hydrazinocurcumin exhibits potent suppressive activity on carcinogenicity of breast cancer cells via STAT3 inhibition

Abstract: Curcumin, the active component of turmeric, has been shown to protect against carcinogenesis and prevent tumor development in cancer. In our study, we tested the efficacy of a synthetic curcumin analogue, known as hydrazinocurcumin (HC), in breast cancer cells. The results demonstrated that compared to curcumin, HC was more effective in inhibiting STAT3 phosphorylation and downregulation of an array of STAT3 downstream targets which contributed to suppression of cell proliferation, loss of colony formation, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…In our previous study, we demonstrated that HC was an effective inhibitor of STAT3 phosphorylation. It could down-regulate an array of STAT3 downstream targets that contributed to the suppression of cell proliferation, loss of colony formation, depression of cell migration and invasion as well as induction cell apoptosis in vitro[13]. Therefore, in this study, HC was employed to suppress STAT3 activity, and re-educate TAMs to change from M2 to M1.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that HC was an effective inhibitor of STAT3 phosphorylation. It could down-regulate an array of STAT3 downstream targets that contributed to the suppression of cell proliferation, loss of colony formation, depression of cell migration and invasion as well as induction cell apoptosis in vitro[13]. Therefore, in this study, HC was employed to suppress STAT3 activity, and re-educate TAMs to change from M2 to M1.…”
Section: Introductionmentioning
confidence: 99%
“…During efficacy testing of hydrazinocurcumin (HC), a synthetic curcumin analogue, inhibition of STAT3 phosphorylation in BC cell lines (MDA‐MB‐231, MCF‐7) decreased the expression of c‐Myc, Bcl‐xL, Bcl‐2, Mcl‐1, cyclin D1/D2, VEGF, MMP‐2 and MMP‐9 among others . Another compound benzyl isothiocyanate (BITC), a constituent of edible cruciferous vegetable, inhibited Leptin stimulated migration and invasion of MDA‐MB‐231 and MCF‐7 human BC cells .…”
Section: Constitutive Activation Of Stat3 and Regulation Of Gene Exprmentioning
confidence: 99%
“…85 During efficacy testing of hydrazinocurcumin (HC), a synthetic curcumin analogue, inhibition of STAT3 phosphorylation in BC cell lines (MDA-MB-231, MCF-7) decreased the expression of c-Myc, Bcl-xL, Bcl-2, Mcl-1, cyclin D1/D2, VEGF, MMP-2 and MMP-9 among others. 86,87 Another compound benzyl isothiocyanate (BITC), a constituent of edible cruciferous vegetable, inhibited Leptin stimulated migration and invasion of MDA-MB-231 and MCF-7 human BC cells. 88 BITC treatment suppressed leptin induced STAT3 phosphorylation and Cyclin D1 transactivation by inhibiting STAT3 recruitment to the Cyclin D1 promoter as detected in chromatin immunoprecipitation (ChIP) analysis.…”
Section: Constitutive Activation Of Stat3 and Regulation Of Gene Exprmentioning
confidence: 99%
“…A study demonstrated that in breast cancer cells, phosphorylated STAT3 up-regulates the EMT associated protein, TWIST (Lo et al, 2007). Further, several studies have demonstrated that STAT3 up-regulates MMP2, MMP7 and MMP9 in breast cancer cell lines Yuan et al, 2008;Wang et al, 2012), proteins that are heavily associated with EMT. Additionally, through regulation of EMT/stemness, STAT3 may also play a role in regulating drug resistance, as it was shown that in human breast cancer, feedback activation of the IL6-STAT3 loop induced EMT and cancer stem cell features, leading to resistance to PI3K inhibitors (Yang et al, 2014).…”
Section: Phosphoinositide 3-kinase (Pi3k)/ Akt/mechanistic Target Of mentioning
confidence: 99%